EFEKTFITAS MENYIKAT GIGI SELAMA 2, 3, DAN 4 MENIT TERHADAP PENURUNAN SKOR DEBRIS PADA SISWA SD BATURAN I GAMPING, SLEMAN YOGYAKARTA TAHUN 2013 - Siti Sulastri; Almujadi Almujadi; Siti Hidayati (Poltekkes Kemenkes Yogyakarta, 2015)
Background: debris/food debris is food residue left onsurface in the mouth and between the teeth and gums/gingival after a person eats, debris can be removed bybrushing is good and right. Recommended brushing teethfor 5 minutes, but generally only 2 minutes. based on preliminarystudies in elementary Baturan I, Gamping, Sleman,Yogyakarta, in October 2012 with interviews and observationsas well as how to brush your teeth checked debris tothe 15 students,75% of students obtained the data is notcorrect way to brush teeth properly and examination scoresdebris on average 0.9Objective: Knowing the effectivenees of brushing for 2minutes, 3 minutes and 4 minutes to the elementary schoolstudents drop debris score Baturan I, Gamping, Sleman,Yogyakarta.Methods: using a pre –experimental research/experimentdesigns one group pretest-postest. Sampling Usingsimple random sampling technique. large sample of 45students. The research hypothesis is brushing for 2 minutesmore effective than tooth brushing for 3 and 4 minutesto decline in debris score of elementary students scoreBaturan I, Gamping, Sleman, Yogyakarta.Results: Test ANOVA the effectiveness of tooth brushingfor 2, 3 and 4 minutes to the decline in debris scores significantdifference(p= 0.000) followed by Post Hoc TukeyHSD, brushing for 3 minutes the most effective/large decreasedebris elementary students score BaturanI,Gamping, Sleman, Yogyakarta(p=0.000).Conclusion: Brushing for 3 minutes is effective/at mostlarge debris lowers score of elementary students BaturanI, Gamping, Sleman, Yogyakarta (p=0.000)